Shakespeare's fugitive politics - Anderson, Thomas Page, 1968- (Edinburgh critical studies in Shakespeare and philosophy., 2016)
Establishes Shakespeare's plays as some of the period's most speculative political literature. Shakespeare's Fugitive Politics makes the case that Shakespeare's plays reveal there is always something more terrifying to the king than rebellion. The book seeks to move beyond the presumption that political evolution leads ineluctably away from autocracy and aristocracy toward republicanism and popular sovereignty. Instead, it argues for affirmative politics in Shakespeare - the process of transforming scenes of negative affect into political resistance. Shakespeare's Fugitive Politics makes the case that Shakespeare's affirmative politics appears not in his dialectical opposition to sovereignty, absolutism, or tyranny; nor is his affirmative politics an inchoate form of republicanism on its way to becoming politically viable. Instead, this study claims that it is in the place of dissensus that the expression of the eventful condition of affirmative politics takes place - a fugitive expression that the sovereign order always wishes to shut down. Key Features. Promotes a new understanding of 'fugitive democracy' Establishes the presence of a form of alternative politics in early modern drama, articulated through the contours of theories of sovereignty Explores how the parameters of contemporary radical politics take shape in major Shakespeare plays, including Coriolanus, King John, Henry V, Titus Andronicus, The Winter's Tale and Julius Caesar Shakespeare's Fugitive Politics makes the case that Shakespeare's plays reveal there is always something more terrifying to the king than rebellion. The book seeks to move beyond the presumption that political evolution leads ineluctably away from autocracy and aristocracy toward republicanism and popular sovereignty. Instead, it argues for affirmative politics in Shakespeare - the process of transforming scenes of negative affect into political resistance. Shakespeare's Fugitive Politics makes the case that Shakespeare's affirmative politics appears not in his dialectical opposition to sovereignty, absolutism, or tyranny; nor is his affirmative politics an inchoate form of republicanism on its way to becoming politically viable. Instead, this study claims that it is in the place of dissensus that the expression of the eventful condition of affirmative politics takes place - a fugitive expression that the sovereign order always wishes to shut down.